Adult turner syndrome – a family physician’s perspective - Shariff Ghazali, Sazlina; Ahmad, Zaiton (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2006)
This patient had delayed puberty and was diagnosed as having Turner syndrome in adulthood. There are multiple issues to be addressed, not just the medical conditions and the ovarian failure but also the fertility options, the psychosocial aspects and the religious issues that present with the condition. As a family physician, many important issues need to be addressed, taking a holistic approach to ensure comprehensiveness and continuity of care.